CoLab-Res: AN INTEGRATED MULTILEVEL FRAMEWORK FOR THE DIAGNOSIS, ASSESSMENT, AND ENHANCEMENT OF INTERPROFESSIONAL EDUCATION IN MULTIPROFESSIONAL HEALTH RESIDENCY PROGRAMS - Ana Paula Oliva Reis; Márcia Bitar Portella (Artefactum - revista de estudos interdisciplinares, 2026)
The incorporation of Interprofessional Education (IPE) into Multiprofessional Health Residency Programs depends on the articulation of individual competencies, institutional conditions, curricular coherence, and pedagogical strategies. This article aims to present CoLab-Res, an integrated multilevel framework developed to analyze and support the incorporation of IPE into these programs. The framework was developed through an integrative literature review, documentary analysis of political-pedagogical projects, and a critical synthesis of national and international frameworks, with the identified gaps translated into four operational questions. CoLab-Res comprises four interconnected technologies: RECI-Res, which defines interprofessional competencies and progression levels; IMIEIP-Res, which assesses the institutionalization of IPE in political-pedagogical projects; MACCI-Res, which compares the prescribed and experienced curriculum; and ATLAS-Res, which provides pedagogical strategies to address identified weaknesses. The three diagnostic and assessment components underwent content validation using an adapted Delphi technique with 13 experts, achieving final content validity indices of 0.96, 0.92, and 0.96, respectively; ATLAS-Res was evaluated by 17 experts and achieved a final content validity index of 0.92. Integrated, these components structure a cycle of defining, diagnosing, verifying, intervening, and reassessing. CoLab-Res proposes that interprofessionality be understood as a progressive and multilevel process, moving it beyond a solely normative dimension and making it an object of pedagogical management. Multicenter and longitudinal studies are needed to examine its external validity, responsiveness, transferability, and effects on educational and healthcare processes.